HIV prevalence and uptake of HIV/AIDS services among youths (15–24 Years) in fishing and neighboring communities of Kasensero, Rakai District, South Western Uganda - Mafigiri, Richardson; Matovu, Joseph K. B.; Makumbi, Fredrick E.; Ndyanabo, Anthony; Nabukalu, Doreen; Sakor, Moses; Kigozi, Godfrey; Nalugoda, Fred; Wanyenze, Rhoda K. (BMC public health, 2017)
Although fishing communities have a significantly higher HIV prevalence than the general population, there is paucity of data on the burden of HIV and service utilization, particularly among the youth. We assessed the HIV prevalence and utilization of HIV prevention and treatment services among youth in Kasensero fishing community and the neighboring communities. Method Data were derived from the Rakai Community Cohort Study (RCCS) surveys conducted between 2013 and 2014. The RCCS is a population-based household survey that collects data annually from individuals aged 15–49 years, resident in 48 communities in Rakai and neighboring districts in Uganda. For this analysis, socio-demographic, behavioral and HIV-related data were obtained for 792 individuals aged 15–24 years. We used logistic regression to conduct bivariate and multivariable analysis to determine the factors that are independently associated with HIV-positive status and their corresponding 95% confidence intervals. Data were analyzed using STATA version 13. Results Overall HIV prevalence was 19.7% (n = 155); higher in Kasensero (n = 141; 25.1%) and Gwanda (n = 8; 11%) than in Kyebe (n = 6; 3.9%), p < 0.001 and among females (n = 112; 26.0%) than males (n = 43; 12.0%), p < 0.001. Uptake of HIV testing was high in both HIV-positive (n = 136; 89.5%) and HIV-negative youth (n = 435; 92%). Consistent condom use was virtually non-existent in HIV-positive youth (n = 1; 0.6%) compared to HIV-negative youth (n = 20; 4.2%). Only 22.4% (n = 34) of the HIV-positive youth were receiving antiretroviral therapy (ART) in 2013–2014; higher in the HIV-positive females (n = 31; 28.4%) than HIV-positive males (n = 03; 6.7%). Slightly more than half of males (n = 134; 53.8%) reported that they were circumcised; the proportion of circumcised youth was higher among HIV-negative males (n = 122; 58%) than HIV-positive males (n = 12; 27.9%). Factors significantly associated with HIV-positive status included living in Kasensero landing site (adjusted Odds Ratio [aOR] = 5.0; 95%CI: 2.22–13.01) and reporting one (aOR = 5.0; 95%CI: 1.33–15.80) or 2+ sexual partners in the past 12 months (aOR = 11.0; 95% CI; 3.04–36.72). Conclusion The prevalence of HIV is high especially among young females and in landing site communities than in the peripheral communities. Uptake of HIV prevention and treatment services is very low. There is an urgent need for youth-friendly services in these communities.